Siege of Washington, D.C., written expressly for little people - Adams, F. Colburn (Francis Colburn), 1850-1891 (Salt Lake City, UT : Project Gutenberg, 2003)
"Siege of Washington, D.C." written expressly for little people by F. Colburn Adams is a historical account likely penned in the late 19th century. The book humorously addresses an important military event during the American Civil War, specifically the defense of the capital, Washington, D.C., against Confederate forces. Through a whimsical tone, it aims to both inform and entertain younger readers, blending historical facts with lighthearted commentary on the absurdities of war and its characters. The opening of the book sets the stage by introducing Washington, D.C., as a unique and somewhat chaotic city, reminiscent of Rome saved by a goose. Adams promises to detail how Washington was saved, foreshadowing an entertaining juxtaposition where a barrel of whisky is humorously suggested as the savior of the capital. The narrative begins with anecdotes and observations about the city's peculiarities and life, while touching upon the grim realities of slavery that prompted the war. Adams expresses his intention to present a straightforward account of the siege, interspersed with humor, thus providing a lighter perspective on a pivotal moment in American history. (This is an automatically generated summary.)
Release date is 2003-11-01
This etext was created by Charles Aldarondo
Keywords: United States -- History -- Civil War, 1861-1865 -- Caricatures and cartoons; Washington (D.C.) -- History -- Civil War, 1861-1865